Science Fictions: Figuring Autism as Threat and Mystery in Medico-Therapeutic Literature - Bill Rocque (Disability Studies Quarterly, 2009)
This paper explores the figuring of autism as both threat and mystery within medico-therapeutic discourses. These figurations carry powerful meanings that may be drawn upon to further scientific, therapeutic and political projects. Despite having its origin in the “helping professions,” such imagery is damaging to people with autism, but it does not stand uncontested. Counter-figurations--representations offered by people labeled autistic and their allies--challenge dominant medico-therapeutic narratives in order to make positive self-definition possible. Contestation over the meaning of autism pointedly demonstrates that, despite being a biogenetic condition, ASD has clear sociocultural and political dimensions that affect how neurotypicals act toward those labeled autistic.